Pengaruh Profitabilitas Dan Leverage Terhadap Financial Distress Pada Perusahaan Sub Sektor Barang Kimia Dasar Dan Sub Sektor Barang Kimia Khusus - Egi Gumala Sari; Aditya Widiyanto (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – This study aims to determine the effect of Profitability andLeverage on Financial Distress.Design/methodology/approach – This research uses quantitative data, thesample in this study is sub-sector basic chemical materials and sub-sectorspecialty hemical materials companies which are listed on the Indonesia StockExchange in the period 2018 – 2022 as many as 11 companies. The analysistechnique used to test the hypothesis is multiple regression analysis usingEviews 9 software.Findings – The results of this study indicate that the Profitability variable hasa negative and statistically insignificant effect on Financial Distress, Leveragevariable has a negative and statistically significant effect on FinancialDistress.Originality/value - This study discusses Financial Distress and otherfactors such as Profitability and Leverage which focus on sub-sector basicchemical materials and sub-sector special chemical materials companies. Thisstudy uses the Altman Z-